1972
DOI: 10.3382/ps.0512106
|View full text |Cite
|
Sign up to set email alerts
|

Receptiveness of Salmonella and Arizona Strains to R Factor from Escherichia Coli in Vitro

Abstract: Twelve antibiotic-sensitive strains of Arizona and ten of Salmonella were tested for ability to receive drug resistance in vitro from two multiple resistant, R factor-carrying strains of E. coli isolated from soiled eggs. Eleven of the 12 Arizona strains and 8 of the 10 Salmonella strains received the R factor from at least one of the donor E. coli strains. One of the donor strains transferred only part of its drug resistance pattern to some of the sensitive strains. ABSTRACTChicks were hatched from S.C.W.L. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Resistance plasmids have been demonstrated to be conjugatively transmissible in vitro at a high frequency (Lakhotia et al, 1972;Nivas et al, 1976). Such transfer has been shown to occur both within and between species.…”
Section: Introductionmentioning
confidence: 96%
“…Resistance plasmids have been demonstrated to be conjugatively transmissible in vitro at a high frequency (Lakhotia et al, 1972;Nivas et al, 1976). Such transfer has been shown to occur both within and between species.…”
Section: Introductionmentioning
confidence: 96%
“…The rate of recovery of SAr from poults given no antibiotic in that study was much higher than that observed for the S7r recipient culture in the present study, suggesting that ST is a less effective plasmid recipient than SA. Variations in recipient competence between Salmonella strains have been previously reported (Lakhotia et al, 1972;Gast and Stephens, 1985). Differences in the abilities of various bacterial strains to act as recipients for the transfer of resistance genes can be due to a number of factors, including the presence of restriction systems that encode enzymes to degrade unmodified incoming DNA molecules (Lyon and Skurray, 1987).…”
Section: Discussionmentioning
confidence: 96%
“…Conjugative transfer of resistance has been shown to occur in vitro at a high frequency (Lakhotia et al, 1972;Nivas et al, 1976 vivo transfer, however, has not been consistently demonstrated. Environmental factors such as temperature have been found to restrict the frequency of transfer in vivo (Smith, 1970).…”
Section: Introductionmentioning
confidence: 95%